Talak Online Dalam Tinjauan Fiqh Munakahat Dan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Harry Kurniawan; Yulia Putri SDW (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
The use of technology in this era of globalization can indeed be said to be unlimited, all people in the world are able to access technology without knowing space and time. One type of contract that is affected by technological advances itself is divorce through social media. The issue of divorce via social media has begun to spread from the upper to the lower classes in Indonesia. In this era of globalization, the phenomenon of severing marriage bonds is found which is not only said directly but through electronic media and other social media. The purpose of this study is to determine the Review of Islamic Law on Divorce through Online Media, and to determine the Review of Marriage Law on Divorce through Online Media. The research method used in this thesis is the library research method. The results of this study are the Review of Islamic Law on Divorce through online media, namely the Law of Divorce through online media can be analogized/equated with divorce through ordinary written letters (bil kitabah). Because there are similarities between the two, the Review of Marriage Law on divorce through online media is, the law of divorce outside the court is only valid according to religious law, but is not valid according to the law in force in the Republic of Indonesia. The consequence of divorce carried out outside the court is that the marriage bond between the husband and wife has not been legally terminated. The suggestion from this study is that it would be good if the current technological developments could be responded to wisely so that technology users can have a positive influence on the development of the nation and state. It is better if the issue of divorce is not carried out arbitrarily, divorce should be carried out without violating positive law or Islamic law.